The Effect of Net Income and Dividends on Stock Prices at PT Telkom Indonesia Tbk in 2018-2022 - Rulis Setyowati; Vivi Ade Rivani; Yunita Budi A M; Maria Yovita R.Pandin (Finance : International Journal of Management Finance, 2023)
This research aims to analyze the effect of net profit and dividends on share prices at PT Telkom Indonesia Tbk during the period 2018 to 2022. The data used is company financial data which includes net profit, dividends and share prices. The research method applied is quantitative, Quantitative methods are a type of research that is more organized and methodical in terms of the use of numbers, as well as more clear and precise in the way it collects data and presents its findings. The research results show that net profit has a positive and insignificant influence on the share price of PT Telkom Indonesia Tbk. This shows that the higher the company's net profit, the higher the share price, but there are insignificant influencing factors such as economic conditions, industry competitors and so on. Dividends also have a positive and insignificant influence on the company's share price. This means that the higher the dividend distributed, the higher the share price of PT Telkom Indonesia Tbk. Apart from that, net profit and dividends have a positive and insignificant influence on share prices. This research provides a better understanding of the factors that influence company share prices and can be a reference for investors and shareholders in making investment decisions.